The Association of Enhanced Recovery Pathway and Acute Kidney Injury in Patients Undergoing Colorectal Surgery. Issue 2 (February 2020) - Wiener, Jameson G.D.; Goss, Lauren; Wahl, Tyler S.; Terry, Morgan A.; Burge, Kaitlin G.; Chu, Daniel I.; Richman, Joshua S.; Cannon, Jamie; Kennedy, Gregory D.; Morris, Melanie S.
Abstract : BACKGROUND: Acute kidney injury is associated with increased postoperative length of hospital stay and increases the risk of postoperative mortality. The association between the development of postoperative acute kidney injury and the implementation of an enhanced recovery after surgery protocol remains unclear. OBJECTIVE: This study aimed to examine the relationship between the implementation of an enhanced recovery pathway and the development of postoperative acute kidney injury. DESIGN: In this retrospective cohort study, a prospectively maintained database of patients who underwent elective colorectal surgery in an enhanced recovery pathway were compared to a hospital historical National Surgical Quality Improvement Program colorectal registry of patients. SETTINGS: This study was conducted at the University of Alabama at Birmingham, a tertiary referral center. PATIENTS: A total of 1052 patients undergoing elective colorectal surgery from 2012 through 2016 were included. MAIN OUTCOME MEASURES: The development of postoperative acute kidney injury was the primary outcome measured. RESULTS: Patients undergoing an enhanced recovery pathway had significantly greater rates of postoperative acute kidney injury than patients not undergoing an enhanced recovery pathway (13.64% vs 7.08%; p < 0.01). Our adjusted model indicated that patients who underwent an enhanced recovery pathway (OR, 2.31; 95% CI, 1.48–3.59; p < 0.01) had an increased risk of acute kidney injury. Patients who developed acute kidney injury in the enhanced recovery cohort had a significantly longer median length of stay than those who did not (median 4 (interquartile range, 4–9) vs 3 (interquartile range, 2–5) days; p =0.04). LIMITATIONS: This study did not utilize urine output as a modality for detecting acute kidney injury. Data are limited to a sample of patients from a large academic medical center participating in the National Surgical Quality Improvement Program. Interventions or programs in place at our institution that aimed at infection reduction or other initiatives with the goal of improving quality were not accounted for in this study. CONCLUSION: The implementation of an enhanced recovery after surgery protocol is independently associated with the development of postoperative acute kidney injury. See Video Abstract at http://links.lww.com/DCR/B69 . LA ASOCIACIÓN DE VÍA DE RECUPERACIÓN MEJORADA Y LESIÓN RENAL AGUDA EN PACIENTES DE CIRUGÍA COLORRECTAL: ANTECEDENTES: La lesión renal aguda se asocia con una mayor duración en la estancia hospitalaria y aumenta el riesgo de la mortalidad postoperatoria. La asociación entre el desarrollo de la lesión renal aguda postoperatoria y la implementación de un protocolo de Recuperación Mejorada después de la cirugía, sigue sin ser clara. OBJETIVO: Examinar la relación entre la implementación de una vía de Recuperación Mejorada y el desarrollo de lesión renal aguda postoperatoria. DISEÑO: Estudio de cohorte retrospectivo, de una base de datos mantenida prospectivamente, de pacientes que se sometieron a cirugía colorrectal electiva, en una vía de Recuperación Mejorada, se comparó con el registro histórico de los pacientes colorrectales del Programa Nacional de Mejora de la Calidad Quirúrgica. AJUSTES: Universidad de Alabama en Birmingham, un centro de referencia terciario. PACIENTES: Un total de 1052 pacientes sometidos a cirugía colorrectal electiva desde 2012 hasta 2016. PRINCIPALES MEDIDAS DE RESULTADO: Desarrollo de lesión renal aguda postoperatoria. RESULTADOS: Los pacientes sometidos a una vía de Recuperación Mejorada, tuvieron tasas significativamente mayores de lesiones renales agudas postoperatorias, en comparación con los pacientes de Recuperación no Mejorada (13.64% vs 7.08%; p < 0.01). Nuestro modelo ajustado indicó que los pacientes que se sometieron a una vía de Recuperación Mejorada (OR, 2.31; IC, 1.48–3.59; p < 0.01) tuvieron un mayor riesgo de lesión renal aguda. Los pacientes que desarrollaron daño renal agudo en la cohorte de Recuperación Mejorada, tuvieron una estadía mediana significativamente más larga en comparación con aquellos que no [mediana 4 (rango intercuartil (RIC) 4–9) versus 3 (RIC 2–5) días; p = 0.04]. LIMITACIONES: Este estudio no utilizó la producción de orina como una modalidad para detectar daño renal agudo. Los datos se limitan a una muestra de pacientes de un gran centro médico académico, que participa en el Programa Nacional de Mejora de la Calidad Quirúrgica. Las intervenciones o programas implementados en nuestra institución, destinados a la reducción de infecciones u otras iniciativas, con el objetivo de mejorar la calidad, no se tomaron en cuenta para este estudio. CONCLUSIÓN: La implementación de una Recuperación Mejorada después del protocolo de cirugía, se asocia independientemente con el desarrollo de lesión renal aguda postoperatoria. Consulte Video Resumen en http://links.lww.com/DCR/B69 . ( Traducción—Dr. Fidel Ruiz-Healy )